Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10072-020-04693-y
|View full text |Cite|
|
Sign up to set email alerts
|

Guillain-Barre syndrome during COVID-19 pandemic: an overview of the reports

Abstract: Similar to severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), the coronavirus disease 2019 (COVID-19) has neurological symptoms. COVID-19 patients have such clinical symptoms as headache, vomiting, nausea, dizziness, myalgia, anosmia, ageusia, and disorder of consciousness. These symptoms confirm that the nervous system is involved in the COVID-19 infection. Guillain-Barré syndrome (GBS) is a heterogeneous disorder which often follows a viral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
1
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 64 publications
2
106
1
15
Order By: Relevance
“…We present these five cases of an acute and mild peripheral and autonomic nervous system dysfunction probably due to a SARS-CoV-2 infection. Although several cases have been published [2][3][4][5][6][7][8][9], most of them are described in patients with severe forms of COVID-19 and the polyneuropathy is also a serious complication that required hospital admission and immunoglobulin treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We present these five cases of an acute and mild peripheral and autonomic nervous system dysfunction probably due to a SARS-CoV-2 infection. Although several cases have been published [2][3][4][5][6][7][8][9], most of them are described in patients with severe forms of COVID-19 and the polyneuropathy is also a serious complication that required hospital admission and immunoglobulin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Most of them are severe polyneuropathies in a severe lower respiratory tract infection. Many of these patients required ventilatory support and immunoglobulin treatment [2][3][4][5][6][7][8][9]. Recent studies support the association between GBS and COVID-19 [10,11], although one analysis did not find this association [12].…”
Section: Introductionmentioning
confidence: 99%
“…The age of patients ranged from youngest 5 years to oldest 84-yearold. 9 Abdelhady et al reported 1 st case of transverse myelitis in a 52-year-old male patient with acute COVID-19 infection. 10 Our patient presented with flaccid symmetrical paralysis involving both lower limbs along with bladder and bowel involvement favoring clinical diagnosis of ATM though we could not further investigate her as the patient went LAMA.…”
Section: Casementioning
confidence: 99%
“…Acute flaccid palsy as a manifestation of COVID-19 infection in acute stage and also as a late manifestation. [8][9][10] Curtis et al reported 1 st case of GBS with COVID-19 infection in a 8 year old child. 8 Review article by Rahimi highlighted possible link between GBS and COVID-19 infection from case reports around the word.…”
Section: Casementioning
confidence: 99%
“…The other coronavirus (SARS-CoV and MERS) and Zika virus have also been associated with GBS [ 8 ]. Therefore, since the start of pandemic, many cases with close association between COVID-19 and GBS incidence have been reported worldwide [ 9 ]. The pathogenesis of COVID-19 and GBS (or other immune neurological conditions) can be linked to systemic inflammation and immune dysregulation mechanism in which there is a maladaptive immune response characterized by hyperactivity of innate immunity followed by immunosuppression [ 10 ].…”
Section: Introductionmentioning
confidence: 99%